2005
DOI: 10.1007/s00441-004-1071-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased uptake of folate conjugates by activated macrophages in experimental hyperlipemia

Abstract: In the pathogenesis of atherosclerosis, macrophages become activated and play a crucial role in plaque formation. Activated synovial macrophages have recently been shown to express receptors for folic acid. We have determined whether activated macrophages also over-express folate receptor (FR) in atherosclerosis. Most normal cells express little or no FR, and, if FR is present on activated macrophages, folate-linked compounds and drugs could be selectively targeted to those cells that do express FR. To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
2
25
1
Order By: Relevance
“…5). These observations are consistent with previous histologic data on atherosclerotic heart valves from Syrian golden hamsters, which suggested that lipidladen macrophage foam cells can be readily targeted with folate-Texas Red (26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5). These observations are consistent with previous histologic data on atherosclerotic heart valves from Syrian golden hamsters, which suggested that lipidladen macrophage foam cells can be readily targeted with folate-Texas Red (26).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, together with the previously published data on osteoarthritis (12) and rheumatoid arthritis (14,23), the evidence presented here documents a third inflammatory disease that can be visualized with an FR-targeted radioimaging agent (26,40). Because many other inflammatory diseases are also characterized by a localized accumulation of activated macrophages, it will be important to determine whether similar folate conjugates might prove useful in imaging these other inflammatory diseases as well.…”
Section: Discussionsupporting
confidence: 60%
“…It is also possible that folate-PEG-Chol targeted liposomes were more easily captured by the FR on activated macrophage, which can be utilized for treatment chronic inflammatory diseases such as rheumatoid arthritis. [67][68][69][70] In summary, we have prepared and evaluated FR-targeted liposomes incorporating cholesterol derivatives mPEG-Chol and F-PEG-Chol. The particle properties, such as the morphology, stability, in vitro release, targeting efficacy, and in vivo circulation were evaluated in parallel with liposomes containing DSPE-anchored derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies on animal hyperlipidemic models demonstrated increased uptake of folate conjugates by activated macrophages The systemically administered folatefluorescent conjugates accumulated in protrusions of atherosclerotic plaques populated by macrophages, suggesting that activated macrophages can be efficiently targeted ''in vivo'' by using folate conjugate (Antohe et al, 2005a). Extensive atherosclerotic lesions were detected in sections of the aortic arch and cardiac valves that were packed with lipid deposits as revealed by staining with Oil Red O ( Figure 1a).…”
Section: Folate and Folate Receptors In Atherosclerosismentioning
confidence: 93%